Volcanic risk management practice evolution between vulnerability and resilience: The case of Arequipa in Peru - Lièvre, Pascal; Mérour, Eléonore; Morin, Julie; Macedo Franco, Luisa; Ramos Palomino, Domingo; Rivera Porras, Marco; Masías Alvarez, Pablo; van Wyk de Vries, Benjamin (Frontiers in Earth Science, 2022)
This paper proposes a new way of understanding the debate between vulnerability and resilience. We mobilize on the theoretical level the notion of "paradigm" in the sense of Kuhn and, on the methodological level, Foucault's notion of "apparatus" to understand volcanic risk management practices. Through an interdisciplinary approach, combining management, geography and Earth sciences, we study the evolution of volcanic risk management practice in Arequipa (Peru) from the 1990s to present. To do this, we look at the history of volcanic risk management in Arequipa, using a qualitative interview methodology based on 6 in-depth centered interviews from the main actors of this history, supported by a two-month ethnography which allowed to access to a large institutional documentation (reports, studies, archives, maps, pictures...). Management practices in Arequipa appear to be centered on the paradigm of vulnerability since the 1990s. Some operations since 2015 named as resilient emerge but they are still inscribed in the vulnerability paradigm. The results show the relevance of the theoretical and methodological framework chosen for Arequipa but also the possibility of using it in a more general way.